Endoscopic fiber probe for nonlinear spectroscopic imaging - Lukic, Aleksandar; Dochow, Sebastian; Bae, Hyeonsoo; Matz, Gregor; Latka, Ines; Messerschmidt, Bernhard; Schmitt, Michael; Popp, Juergen (Optica, 2017)
We present a compact multimodal fiber probe that enables the simultaneous recording of nonlinear imaging modalities like coherent anti-Stokes Raman scattering (CARS), second harmonic generation (SHG), and two-photon excited auto-fluorescence (TPEF) for biomedical applications. The probe is based on a gradient index lens design and a multi-core fiber supplying the excitation laser light. The multi-core fiber preserves the spatial relationship between the entrance and output; therefore, the laser scanning procedure can be shifted from the distal to the proximal end of the probe. No moving parts or electric power are required in situ. The generated sample signals can be collected in the backward (epi) direction and transferred to a detection setup with a multimode fiber integrated in the probe head. The first CARS/SHG/TPEF multimodal tissue images recorded with the introduced fiber probe will be presented.
CRIS-Team Scopus Importer:2023-04-20